Orthodontic Treatment Need in Bangladeshi Young Adults Evaluated Through Dental Aesthetic Index (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2015)
Aim : The objectives of this study were to evaluate the severity of malocclusion and orthodontic treatment need in Bangladeshi young adults by using the Dental Aesthetic Index (DAI).Methods: This cross-sectional study was conducted at Government and private college of Dhaka and Netrokona, Bangladesh. A total of 405 students (from 17 to 25 years old) were selected by convenience sampling. Students wearing orthodontic appliance or reporting a history of orthodontic treatment were excluded from the study. Clinical examinations were conducted using the Dental Aesthetic Index (DAI). The chi-square test (x2) was used to compare malocclusion severity. The analysis of variance (ANOVA) test was used to compare the changes in DAI scores and the mean DAI scores between various age groups. The t test was used to compare the mean DAI scores between sex groups.Results: 405 college students were examined, 305(75.3%) were boys and 100(24.7%) were girls. Most of the  students 277(68.4%) had DAI scores ? 25 with no or little malocclusion requiring slight  or no  orthodontic  treatment, 76(18.8%) had DAI score of 26-30 with definite malocclusion requiring elective orthodontic  treatment, 34(8.4%) had DAI score of 31-35 with severe type of malocclusion requiring highly desirable orthodontic treatment, 18(4.4%) had DAI score ? 36 with very severe or handicapping malocclusion requiring mandatory orthodontic treatment.Conclusion: The majority of the students in our study (68.4%) required no or little treatment; (12.8%) had definite malocclusion requiring definite orthodontic treatment.Ban J Orthod & Dentofac Orthop, April 2013; Vol-3, No.2